Vaccination decision-making among mothers of children 0-12 months old in Nigeria: A qualitative study - Gbadebo Collins Adeyanju; Cornelia Betsch (Taylor & Francis Group, 2024)
The contribution of vaccination to global health, especially in low-middle-income countries is one of the achievements in global governance of modern medicine, averting 2-3 million child deaths annually. However, in Nigeria, vaccine-preventable-diseases still account for one-in-eight child deaths before their fifth-year birthday. Nigeria is one of the ten countries where 4.3 million children under five are without complete immunization. Therefore, the goal of this contribution is to shed light on the reasons to set a foundation for future interventions. To conduct focus groups, a simplified quota sampling approach was used to select mothers of children 0-12 months old in four geographical clusters of Nigeria. An interview guide developed from the 5C psychological antecedence model was used (assessing confidence, complacency, calculation, constraints, collective responsibility); two concepts were added that had proved meaningful in previous work (religion and masculinity). The data were analyzed using a meta-aggregation approach. The sample was relatively positive toward vaccination. Still, mothers reported low trust in vaccine safety and the healthcare system (confidence). Yet, they had great interest in seeking additional information (calculation), difficulties in prioritizing vaccination over other equally competing priorities (constraints) and were aware that vaccination translates into overall community wellbeing (collective responsibility). They had a bias toward God as ultimate giver of good health (religion) and their husbands played a dominant role in vaccination decision-making (masculinity). Mothers perceived their children vulnerable to disease outbreaks, hence, motivated vaccination (complacency). The study provided a useful qualitative tool for understanding mothers' vaccination decision-making in low resources settings.